(untitled) (Al Basirah, 2020)
This research clarifies the concept of Islamic Heritage, its importance, benefits, divisions, and the West’s position towards this original heritage, and how it is considered one of the most important components of the general Islamic culture. This heritage that we inherited from the forefathers is considered one of the most important sources of Islamic culture that relied on drawing its characteristics on the original sources of Islam, and with this specificity the Islamic culture was distinguished similarly like Islamic legislations and unlike the other man- made laws that are subject to deficiency, ruin , destruction and ending, the Islamic culture was based in its sources on the Holy Qur’an and the noble Prophet’s Sunnah, therefore, its characteristics were consistent with the characteristics of Islam because of its close connection with it in terms of source, strength, taking , survival , continuity and empowerment, and because it carries its approach, goals and objectives in which the Islamic culture absorbs all different aspects of life from foreign policy, internal governance, judiciary, administration, economics, social aspects, transactions and worship, and many other diverse areas in people’s individual or social lives, thus, it is surrounded by man in different stages of his life from birth, childhood and manhood, and in his relationships needs internally and externally and all of these can be discussed in terms of authenticity of Islamic Heritage, because it is considered one of the most important topics that the Islamic culture taken care of by research and study through the sources, bases, characteristics, goals and effects on individual and society and directs it in all matters of life.